FREQUENCY OF PRIMARY SOLID MALIGNANT NEOPLASMS IN DIFFERENT AGE GROUPS AS SEEN IN OUR PRACTICE - Ahmed, Zubair; Azad, Najamul Sahar; Rauf, Fouzia; Yaqoob, Nausheen; Husain, Akthar; Ahsan, Aamir; Ahmed, Rashida; Kayani, Naila; Pervez, Shahid; Hassan, Sheema H (Journal of Ayub Medical College Abbottabad, 2007)
Background: To determine in a large series of surgical biopsies, the frequency of various histologic types of primary solid malignant neoplasms in males and females in different age groups. Methods : A retrospective study of 20,000 consecutive surgical biopsies reposted in the section of histopathology, AKU in 2004. Results: Malignant neoplasms are commonest in the fifth and sixth decades of life. The commonest malignant neoplasms in the first decade were Hodgkin's lymphoma and Wilm's tumor in males and females respectively. In the second decade, osteosarcoma in males and Ewing's sarcoma / PNET in females. In the third decade, colorectal adenocarcinoma in males and infiltrating Ductal carcinoma of breast in females. In the fourth decade, squamous cell carcinoma of oral cavity in males and infiltrating ductal carcinoma of breast in females. In the fifth decade squamous cell carcinoma of oral cavity in males and infiltrating ductal carcinoma of breast in females. In sixth decade, squamous cell carcinoma of oral cavity in males and infiltrating ductal carcinoma of breast in females and in the seventh decade, prostatic adenocarcinoma in males and infiltrating ductal carcinoma of the breast in females. Above age of 70 years, the commonest malignant were again prostatic adenocarcinoma in males and infiltrating ductal carcinoma of breast in females. Conclusion: Malignant neoplasms are commonest in the fourth, fifth and sixth decades of life.